2006
DOI: 10.3832/efor0407-0030588
|View full text |Cite
|
Sign up to set email alerts
|

Juglans regia L. tree plantations for wood production in mining area of S. Barbara (AR). Evaluation of N-fixing accessory trees effect

Abstract: Juglans regia L. tree plantations for wood production in mining area of S. Barbara (AR). Evaluation of N-fixing accessory trees effect.The study was carried out in experimental plots located in the Arno valley (Cavriglia, province of Arezzo -Italy). The experimental plots, walnut (Juglans regia L.) plantations both pure and mixed to accessory trees (Alnus cordata Loisel., Corylus avellana L., Eleagnus angustifolia L. and Robinia pseudoacacia L.), were established in 1986 and 1989. Data on grown and architectur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
4
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 7 publications
4
4
0
5
Order By: Relevance
“…Growth was usually slow during the fi rst year, while root system establishment was developing. These fi ndings agree with those of Tani et al ( 2006 ) and Loewe ( 2003 ), who reported best performances in cherry trees grown along with accessory trees, especially N-fi xing species. Therefore, the observed height growth in Chile was greater than in 8 year-old agroforestry plantations in Languedoc, France, where annual height growth ranged between 0.31 and 0.69 m year −1 (Balandier and Dupraz 1999 ).…”
Section: Cherry Growth and Costs In Temperate Agroecosystemsupporting
confidence: 92%
“…Growth was usually slow during the fi rst year, while root system establishment was developing. These fi ndings agree with those of Tani et al ( 2006 ) and Loewe ( 2003 ), who reported best performances in cherry trees grown along with accessory trees, especially N-fi xing species. Therefore, the observed height growth in Chile was greater than in 8 year-old agroforestry plantations in Languedoc, France, where annual height growth ranged between 0.31 and 0.69 m year −1 (Balandier and Dupraz 1999 ).…”
Section: Cherry Growth and Costs In Temperate Agroecosystemsupporting
confidence: 92%
“…Therefore, the observed height growth in Chile was greater than in 8 year-old agroforestry plantations in Languedoc, France, where annual height growth ranged between 0.31 and 0.69 m year −1 (Balandier and Dupraz 1999 ). These fi ndings agree with those of Tani et al ( 2006 ) and Loewe ( 2003 ), who reported best performances in cherry trees grown along with accessory trees, especially N-fi xing species. Positive effects refl ect many cooccurring favorable causes, such as higher nitrogen availability.…”
Section: Cherry Growth and Costs In Temperate Agroecosystemsupporting
confidence: 82%
“…I risultati ottenuti nel loro complesso confermano quanto già emerso in precedenti studi circa il ruolo positivo esercitato dalle specie azoto fissatrici sul l'accrescimento del noce comune (Buresti & De Meo 1999, Tani et al 2006. Prima degli interventi di dira damento i valori complessivi di volume e biomassa degli impianti consociati sono notevolmente superio ri a quelli dell'impianto puro.…”
Section: Discussione E Conclusioniunclassified
“…Dal punto di vista pedologico l'area oggetto di studio rappresenta un ambiente non ottimale per la coltura del noce comune a causa della prevalenza di suoli ar gilloso-limosi, dotati di ph sub-acido, poveri in fo sforo e azoto derivanti dal rimescolamento e succes siva alterazione del materiale di risulta della preesi stente miniera di lignite (Buresti 1986). Per maggiori dettagli circa l'ambiente e le caratteristiche degli im pianti si rimanda a Buresti (1986), Buresti & Fratte giani (1994), Tani et al (2006).…”
Section: Materiale E Metodiunclassified
See 1 more Smart Citation